Komposisi Dan Struktur Vegetasi Riparian Di Kawasan Taman Wisata Gunung Poteng Singkawang Kalimantan Barat - Riza Linda, Imanuel Tiko Junardi Rafdinal (Jurnal Protobiont, 2018)
Riparian ecosystem s an area that has ecological potential in supporting river ecosystems. This area is usually overgrown by various  types of  plants that have adapted  to live in a place that is often inundated by river water, especially when it rains. Research  on the composition and  structure of  riparian vegetation in Mount Poteng area was carried out  in April - June 2017. The method used in this study was a line method with a combination of  paths carried out  in 4 locations. The width of each lane is  20 meters and the length is ± 100 meters. Results of the sample plot of 0.03 ha  in  riparian forest around   the Poteng mountain area found a composition of riparian vegetation consisting of 23 species, 21 genera and 19 families. Araceae family is the family that dominates the Mount Poteng  riparian  area. Tree stand density ranges from 5-60 individuals / ha with diversity index ranging from 0.6 to 1.5.